The Influence of Tourist Motivation, Emotional Experience, and Community Hospitality on Creating Memorable Tourism Experience at the Dieng Plateau - Agya Catur Nugroho; M. Trihudiyatmanto (Universitas Pekalongan, 2026)
This study aims to analyze the influence of tourist motivation, emotional experience, and community hospitality on memorable tourism experience among tourists visiting the Dieng Plateau. A quantitative approach was employed with a population consisting of tourists who had visited Dieng at least twice a year. A total of 112 respondents were sampled using accidental sampling. Data were analyzed using multiple linear regression with SPSS 25. The results indicate that tourist motivation positively affects memorable tourism experience (t = 4.658; sig = 0.000), emotional experience positively influences memorable tourism experience (t = 3.126; sig = 0.000), and community hospitality also positively affects memorable tourism experience (t = 3.413; sig = 0.000). The adjusted R² value of 55.6% shows that the three independent variables jointly explain more than half of the variance in memorable tourism experience, while the remaining 44.4% is influenced by other factors outside this study. These findings suggest that enhancing motivational elements, emotional impressions, and hospitality practices may strengthen visitor satisfaction and foster memorable experiences in tourism destinations. Keywords : Tourist Motivation, Emotional Experience, Community Hospitality, Memorable Tourism Experience